Effects of stingless bee propolis on oxidative stress and structural integrity of heart in streptozotocin-induced diabetic rats - Zhi, Lim Oon (2020)
Diabetes mellitus is a concerning non-communicable disease worldwide that has great socio-economic impact especially in Malaysia where the prevalence beats global figure. Type 1 diabetes mellitus is a chronic metabolic disorder characterised by persistent hyperglycaemia leading to overproduction of oxidative stress that causes diabetic cardiomyopathy. Stingless bee propolis is rich in phenolic compounds that is made of resins from plant exudates and stingless bee’s saliva. It has antihyperglycaemia, antioxidative and antiischemic potential. Nevertheless, no previous study reported the effect of stingless bee propolis on diabetic heart. Thus, this study aims to determine the effect of supplementation of stingless bee propolis on oxidative stress and histopathology of heart in streptozotocin-induced diabetic rats. The polar antioxidative compounds was extracted from raw stingless bee propolis using ethanolic extract. Adult male Sprague Dawley rats was divided into five groups (n=8): normoglycaemia (non-DM), untreated diabetes mellitus (DM), diabetic treated with 300 mg/kg/day metformin (DM+Metformin), diabetic treated with 300 mg/kg/day propolis (DM+Propolis), diabetic treated with both 300 mg/kg/day metformin and 300 mg/kg/day propolis (DM+Combined) and treatment was given on daily basis. Single dose of 60mg/kg streptozotocin was administered intraperitoneally to induce type 1 diabetes mellitus. Treatment was given for four weeks duration following successful induction of diabetes mellitus via oral gavage. Body weight, fasting blood glucose, water intake and food intake were taken every week. The rats were sacrificed after four weeks using 300 mg/kg of sodium pentobarbital. Serum and heart were collected for determination of colourimetric assays (oxidative stress markers and antioxidative enzymes) and histopathology. Diabetic rats experienced manifestation of hyperglycaemia such as polydipsia, polyphagia and weight loss. Their heart contains higher oxidative stress markers and alteration in antioxidative enzymes. Heart of diabetes mellitus rats showed features of diabetic cardiomyopathy including cardiomyocyte hypertrophy, cardiac fibrosis and perivascular fibrosis. Metformin or propolis supplementation reversed the clinical manifestation of diabetic mellitus but propolis alleviated histopathology and biochemical alteration of diabetic cardiomyopathy better than metformin. However, combination of metformin and propolis supplementation observed better improvement than metformin alone. In a nutshell, this study of stingless bee propolis managed to produce positive data on diabetic cardiomyopathy in rats through its antihyperglycaemic and antioxidative properties.